Büs nutag, mongolyn tüühėn dėh barga uls törijn tüüh : (1900-1960 on) = Büse nutuġ, mongġol-un teüken-deki barġu : ulus törü-yin teüke - Mjagmarsambuu, Galindėvijn 1964- (Soëmbo printing HHK, 2017)
Research on the 20th century political history of Barga (region in southern Hulunbuir Shi, China, and southern Dornod Aĭmag, Mongolia)